Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia: All-Russian Scientific Conference with International Participation on Contemporary Issues, 23–27 November 2015, Tomsk, Russia; IOP Conference Series: Earth and Environmental Science (2016, 2016)
Title screen